Convex optimisation based transmit beampattern synthesis for MIMO radar. Issue 9 (4th April 2016) - Pandey, N.; Roy, L. P.
Abstract : A multiple input multiple output (MIMO) radar allows its antenna elements to transmit multiple signal waveforms. This waveform diversity offers enhanced flexibility in transmit beampattern synthesis and signal design. Two algorithms where the transmit is synthesised beampattern by optimising transmitted signal covariance matrix is proposed. In the first algorithm, a method to achieve a desired beampattern by reformulating the design problem as an unconstrained semi‐definite programming problem is proposed. Second, a method for beampattern synthesis such that the cross correlation beampattern, which is the correlation between the signals at different target locations, is minimised and at the same time the sidelobe levels are constrained to be lower than a threshold value proposed. These design problems are modelled as convex optimisation problem and are solved using Matlab based toolbox CVX.